Proposta de sistema para apoio à gestão de competências baseada em sistemas agentes - Czelusniak, Dani Juliano (2007)
Observing the new technologies for software development, an special option that comes gaining prominence, for building software with modules that works in autonomous way. This particular kind of software is called “Agent Systems”. By this way, the goal of this work is to verify the viability of development and tests of a software archetype to aid the competence management process in Post-Graduate of Production Engeneering Courses. This system will be designed using JADE Agent Framework, using the development language C# .NET, to read the XML files exported by the Curriculo Lattes system. In this process, the technologies have been use to build a innovative technology tool that aims the manager to extract some kinds of information, during the seek and analysis process of competence’s indicators. The research methodology used is the bibliographical revision for appraise the theories as competence management and agent systems and state of art when making the proposal, development and tests of the software. This work expose that the agent based methodology can provides satisfactory results for being flexible and to offer forms to deal with human characteristics, beings in a innovative form, creating modular solutions that have the capacity to deal with great databases in a associative form.